Analysis of lateral shear performance of side-toothed hollow slab based on cohesive force constitutive simulation - Songgang Yang; Xiaojuan Shu; Yongguang Li; Mingyan Shen; Chao Zhao (Građevinar)
Herein, based on mortise–tenon hollow slabs, a side-toothed hollow slab structure is proposed for easier lateral connections. Side-tooth structures of both the V- and W-side teeth were constructed. By conducting shear tests on small specimens with different side-tooth shapes, a cohesive constitutive model of epoxy adhesive, which was selected as the inter-tooth bonding material, was developed. The bonding interface was simulated with a zero-thickness epoxy adhesive by using the Voronoi mathematical model for random unit division. A plane micromechanical finite element simulation model was developed using the Abaqus software to analyse the failure modes and shear strength of the hollow slabs with two side-tooth structures under shear action, and the corresponding shear tests were conducted for verification. In the V-side teeth structure, the outer concrete lost its strength earlier and exited the work process, with the height of the cracking shear surface at complete failure being approximately half of the beam height. The W-side teeth joint structure did not exhibit a significant early strength loss during shearing, with the complete shear failure surface being approximately 4/5 of the beam height. The simulation analysis showed larger crack widths during failure in the former and smaller widths in the latter.